The Influence of Store Atmosphere and Location on Purchasing Decisions for Coffee Shop Haidden Sidoarjo - Pratama, Maulana Rifqie; Supriyono, Supriyono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to identify how the influence of Store Atmosphere and Location on purchasing decisions for Coffeshop Haidden Sidoarjo products. The population of this research is consumers of Coffeeshop Haidden Sidoarjo products. This research method is quantitative by taking a sample of 108 respondents and distributing questionnaires in Sidoarjo City with the help of Google Forms. The sample collection technique uses non-probability sampling by determining the accidental sampling method. The sample consists of respondents who live around the City of Sidoarjo, aged 17 years and over, buyers and users of Haidden's Coffeshop products. Data taken from respondents are primary data and secondary data. The analysis technique used in this study uses Partial Least Square (PLS) with validity tests, reliability tests, and hypothesis testing. Based on the results of data processing from this study it can be concluded that the decision to purchase Coffeshop Haidden products is positively and significantly influenced by the Store Atmosphere and Location variables.